Do Investment-Based Models Explain Equity Returns? Evidence from Euler Equations. (27th September 2021) - Delikouras, Stefanos; Dittmar, Robert F
Abstract: We investigate the empirical implications of the investment-based model of asset pricing for the Hansen-Jagannathan and Kozak-Nagel-Santosh discount factors in the linear span of equity returns. We find that the stochastic discount factors satisfying the Euler equation for equity returns cannot satisfy the Euler equation for investment returns because returns on corporate investment covary inversely with the sources of equity risk relative to returns on equity. As a result, the model fails to replicate the level of the risk premium. Our results suggest that joint restrictions on the optimality of investment and consumption pose stringent conditions for candidate production models.